1970
DOI: 10.1084/jem.132.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Function in Anti-Hapten Immune Responses

Abstract: The introduction of defned haptenic determinants into immunogenic carriers by Landsteiner (1) has provided a poweriul tool for the analysis of specific interactions between antigens and specific ceils in the immune response. Considerable evidence has been obtained demonstrating that cellular immune reactions to hapten-protein conjugates (delayed sensitivity [2-@ stimulation of DNA synthesis by antigen [7,8], and hapten-specific secondary responses [9-111) display a significant although variable degree of carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(89 citation statements)
references
References 44 publications
1
88
0
Order By: Relevance
“…affinity of serum anti-DNP antibody for ~-DNP-L-lysine was evaluated by the comparison of antigen-binding capacity in a Farr assay (18) at a standard concentration of bound and free ligand with that at several other concentrations of bound and free ligand, e-DNP-L-lysine-aH (14-25 Ci/mM), prepared as previously described (12,19), at a final concentration of either 0.5 X 10 -a, 0.5 N 10 -7, or 0.5 X 10 -8 M, was mixed with antiserum or antiserum diluted in 10% normal guinea pig serum. After 30 rain, an equal volume of saturated ammonium sulfate was added; 30 rain later the suspension was centrifuged at 2500 rpm at 4°C, and a measured aliquot of supernatant added to 6 ml of Aquasol (New England Nuclear Corp.).…”
Section: Binding Capacity and A~nity Of Serum Anti-dnp Anlibody For ~mentioning
confidence: 99%
“…affinity of serum anti-DNP antibody for ~-DNP-L-lysine was evaluated by the comparison of antigen-binding capacity in a Farr assay (18) at a standard concentration of bound and free ligand with that at several other concentrations of bound and free ligand, e-DNP-L-lysine-aH (14-25 Ci/mM), prepared as previously described (12,19), at a final concentration of either 0.5 X 10 -a, 0.5 N 10 -7, or 0.5 X 10 -8 M, was mixed with antiserum or antiserum diluted in 10% normal guinea pig serum. After 30 rain, an equal volume of saturated ammonium sulfate was added; 30 rain later the suspension was centrifuged at 2500 rpm at 4°C, and a measured aliquot of supernatant added to 6 ml of Aquasol (New England Nuclear Corp.).…”
Section: Binding Capacity and A~nity Of Serum Anti-dnp Anlibody For ~mentioning
confidence: 99%
“…Indeed, the use of complete Freund's adjuvant for sensitization in the studies on the carrier effect induces DH to the carrier (13,16,17). Carrier and hapten determinants are unrelated, separate determinants (14, 17); this conclusion is strongly favored by experiments where tolerance to the carrier reduces the response to the hapten (13,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a cooperating role of anticarrier antibody appears to be invalidated by several experiments (16,17,29). When given passively, anticarrier antibodies either have no effect (6,29) or yield a considerable depression of the antihapten response (16,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Katz et al (10) reported that the primary antihapten antibody response of rabbits and guinea pigs to a hapten coupled to a carrier was enhanced if the animals had been preimmunized with small doses of free carrier. Carrier preimmunization had no effect on the affinity of the antihapten antibody, however.…”
Section: Discussionmentioning
confidence: 99%